The effectiveness of medical nutrition therapy for people at moderate to high risk of cardiovascular disease in an Australian rural primary care setting: 12-month results from a pragmatic cluster randomised controlled trial - Tracy L. Schumacher; Anna Jansson; Jaimee Herbert; Erin D. Clarke; Carissa Alderton; Penny Milson; Christopher Oldmeadow; Leanne J. Brown; Megan E. Rollo; Annabelle Williams; M. Com Nutr; Michelle Guppy; et al. (BMC Health Services Research)
Abstract Purpose To reduce risk of cardiovascular disease (CVD) in adults, as assessed by primary care doctors in rural NSW, Australia. Medical nutrition therapy (MNT) was delivered by Accredited Practicing Dietitians (APDs) using telehealth. Methods The study was a 12-month pragmatic cluster randomised controlled trial. All primary care practices (PCPs) within a large rural region were invited to participate, with enrolled practices stratified based on rurality and practice size. Patients at moderate to high CVD risk were recruited via practices. Usual care (UC) was provided by the patient’s general practitioner (GP). In addition to UC, the intervention group received two hours of MNT telehealth (video calls) consultations from an APD during five sessions over 6 months. The primary outcome was total serum cholesterol. Secondary outcomes included LDL cholesterol, triglycerides, blood glucose control, blood pressure, weight and waist circumference. Changes were analysed using Bayesian linear mixed models and posterior probability. Findings Sixteen PCPs recruited 132 eligible participants (n = 91 intervention, n = 41 UC), with 79% (72/91) and 80% (33/41) respectively completing a primary or secondary outcome. No significant differences were found between groups for total cholesterol, LDL cholesterol or blood pressure at 12-months. However, the intervention group had significant improvements in blood glucose control (HbA1c: -0.16%, 95%CI: -0.32, -0.01) and decreased body weight (-2.46 kg, 95%CI: -4.54, -0.41) compared to UC at 12-months. Conclusions Results indicate that two hours of MNT delivered by an APD via telehealth is a synergistic adjunct therapy to support the usual care provided by GP, with benefits continuing to 12-months.